A pathway to consumer forgiveness in the sharing economy - Shuqair, Saleh (2021)
Shuqair, S., Pinto, D. C., So, K. K. F., Rita, P., & Mattila, A. S. (2021). A pathway to consumer forgiveness in the sharing economy: The role of relationship norms. International Journal of Hospitality Management, 98, 1-8. [103041]. https://doi.org/10.1016/j.ijhm.2021.103041 ---%ABS3%